Stainless steel coupled with carbon nanotube-modified epoxy and carbon fibre composites: Electrochemical and mechanical study*. (15th March 2016) - Baltzis, D.; Orfanidis, S.; Lekatou, A.; Paipetis, A. S.
Abstract : The aim of this work is the study of the electrochemical and mechanical behaviour of stainless steel (SS304) adhesively bonded with carbon nanotube (CNT)-reinforced epoxies to either SS304 or carbon-reinforced composites substrates. For metal to metal (MtM) joints, the shear strength of nano-reinforced adhesives was studied using single lap shear specimen geometries. The lap shear strength was improved by almost 50% and the highest shear strength appeared for 0.6% CNT weight content in the adhesive. The metal to composite joint performed altogether better compared to the MtM joint, although the CNT inclusion had an adverse effect on the lap shear strength attributed to the physical property change of the epoxy. Although the incorporation of CNTs was found to increase the galvanic effect, it also enhanced corrosion protection, as the modified adhesives exhibited increased resistance to uniform corrosion and localised corrosion and prevented the electrolyte from reaching the substrate.